Efficient micromirror confinement of sub-teraelectronvolt cosmic rays in galaxy clusters - Reichherzer, P; Bott, AFA; Ewart, RJ; Gregori, G; Philipp, K; Kunz, MW; Schekochihin, AA (Nature Research, 2025)
Cosmic rays (CRs) play a pivotal role in shaping the thermal and dynamical properties of astrophysical environments, such as galaxies and galaxy clusters. Recent observations suggest a stronger confinement of CRs in certain astrophysical systems than predicted by current CR-transport theories. Here, we show that the incorporation of microscale physics into CR-transport models can account for this enhanced CR confinement. We develop a theoretical description of the effect of magnetic microscale fluctuations originating from the mirror instability on macroscopic CR diffusion. We confirm our theory with large-dynamical-range simulations of CR transport in the intracluster medium (ICM) of galaxy clusters and kinetic simulations of CR transport in micromirror fields. We conclude that sub-teraelectronvolt CR confinement in the ICM is far more effective than previously anticipated on the basis of Galactic-transport extrapolations. The transformative impact of micromirrors on CR diffusion provides insights into how microphysics can reciprocally affect macroscopic dynamics and observable structures across a range of astrophysical scales.